Avenida da Ponte. 1968/2000. Álvaro Siza, a arquitectura e a cidade - Rita Tavares de Almeida Besteiro (2012)
The present study is focused on the act of building in the city by Siza Vieira. We seek to understand is concept of city, and in what way does that concept translate in his works. In fact, after an analysis of his words, we realize that Siza when designing this territory, is constantly seeking the "continuity". Thus, based on this study we list two projects of Siza located in a part of Porto where the lack of continuity is manifested in various spheres, Avenida da Ponte in 1968 and 2000. This part of the city to which we refer was subjected to brutal changes in the forties. These changes had the intention to show the Cathedral, Sé, and at the same time to make the connection between Luis I Bridge, the only entrance by South at the high level, and the new city center, D. Pedro Square, as it was named. The aim was to provide the "second city" of the country with a monumental character similar to what was being done in other major European cities. However, the difficulty of intervening in an irregular and granitic territory combined with the need of full visibility of the cathedral from the low level lead to the non-approval of any project with the exception of the project of Alvaro Siza in 1968. Thus, the Avenue D. Afonso Henriques was opened in the mid fifties, with no concrete plan, which created a wound until today to heal. Is that what Siza aims in 1968 and 2000. He aims to recover what was lost with the demolitions, restoring continuity in a part of town overwhelmed by the sense of rupture. This restoration is done on both projects in very different ways. If in the first project the existing persists almost untouched, of course, different by the presence of the large building on the east. In the second project the city is rebuilt almost literally. In the extreme, it can be said that in the first project, Siza sews the city almost by not building, and so, evoking the memory of the demolitions. In the second one, he heals the wound with the resource of the constructed mass. In both projects what matters is the perception of the city as a territory constructed by many layers. According to Siza none of those layers should be removed. So, he never seeks to erase what happened at that place. The memory of the demolitions is present. Still, as important as knowing what happened there, it is to know what others have projected for that area. So we have tried to find studies that had as scope that place and, above all, those who had the most influence on Siza's projects. Alongside all of this is the unavoidable presence of Fernando Távora both in 1955 and 1998.